Characteristics of Tobacco Stem Particleboard in Printing Load Variations and Storage Time - Winda Amilia; Andrew Setiawan Rusdianto; Whina Sofiana (Journal La Lifesci, 2020)
Tobacco is an important commodity in the economy in Indonesia. Tobacco stems are worthless waste. Tobacco stems contain 56.10% cellulose, making it high potential as a particle board raw material. The process of making particleboard that affects quality is the pressing process during printing. Greater pressure printing presses make bonds between particles stronger. Strong bonding between particles is intended so that the board does not change during storage. The purpose of this study is to determine the characteristics of particleboard in various variations of printing pressure load and storage time and to find out the best treatment as a recommendation in the manufacture of tobacco stem particleboard. The research method was factorial CRD with a combination of treatments between 2 factors namely printing load (4 kg and 8 kg) and storage time (0, 12, and 24 days). The results showed 1.13 - 1.25 g.cm-3 for the density value, water content 4.97 - 12.57%, and water absorption 240.03 - 208.00%. MOE and MOR values ​​were 16000.13 - 36222.77 kgf. cm-2 and 824.47 - 1697.83 kgf.cm-2. The recommended treatment load is 8 kg printing pressure with 12 days of storage time.